A case with unscarred uterus rupture during late postpartum period - Kahyaoglu, Oytun; Pulatoglu, Cigdem; Dogan, Ozan; Yuceer, Deniz (The European Research Journal, 2017)
An unscarred uterus rupture is uncommon. It has non-specific symptoms and presentation differs according to the site and time of rupture. It is usually diagnosed intrapartum or shortly after delivery. Here we report a spontaneous rupture of unscarred uterus with delayed presentation and without any usual risk factors. A 33-year-old and 38 weeks pregnant woman presented with regular uterine contractions. The labor was successfully completed vaginally without any augmentation and no intrapartum complications were observed. After 72 hours the patient complained of an abdominal distension and tenderness. She underwent emergency explorative operation. Intraoperative examination revealed a rupture area on the right posterolateral wall of the uterine fundus approximately 5-6 cm in width. The post-operative period was uneventful and the patient was discharged on 5th postoperative day. Spontaneous rupture of unscarred uterus should be kept in mind even though it is rarely seen complication at late postpartum period.